Pemberdayaan Masyarakat dalam Upaya Restorasi Lahan Pasca Tambang di Desa Bukit Kijang Kecamatan Namang Kabupaten Bangka Tengah - Herdiyanti Herdiyanti; Panggio Restu Wilujeng; Jamillah Cholillah; Laila Hayati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2022)
The program aims to tackle the issue related on the low level of participation of the people in the restoration program on the post-mining land. Empowerment program was provided as the solution to increase the participation level of the people. It was expected that the welfare of the society would improve by utilizing the post-mining land. The beneficiary was people in Desa Bukit Kijang who were affected by the mining activities. Socialization approach was applied related with the effort on restoring the post-mining land. The result of the program was that the participation of the people in the activity had increased. Thus, it was suggested that the policy maker could ensure the empowerment program on the restoration of post-mining land should be massive, systematic and sustainable.